2017
DOI: 10.1152/japplphysiol.00101.2017
|View full text |Cite
|
Sign up to set email alerts
|

The hypoxia-adenosine link during inflammation

Abstract: Hypoxic tissue conditions occur during a number of inflammatory diseases and are associated with the breakdown of barriers and induction of proinflammatory responses. At the same time, hypoxia is also known to induce several adaptive and tissue-protective pathways that dampen inflammation and protect tissue integrity. Hypoxia-inducible factors (HIFs) that are stabilized during inflammatory or hypoxic conditions are at the center of mediating these responses. In the past decade, several genes regulating extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 146 publications
(239 reference statements)
0
87
0
Order By: Relevance
“…With tissue damage, inflammation, and hypoxic stress, ATP is released from stressed, necrotic, and/or apoptotic cells and is hydrolyzed stepwise by ectonucleoside triphosphate diphosphohydrolase-1 (CD39), converting ATP to AMP, and CD73, converting AMP to extracellular adenosine (Figure 1). ATP's activation of ATP receptors promotes inflammation, whereas subsequent breakdown of ATP to extracellular adenosine and activation of adenosine receptors dampens inflammation (Figure 1) (45)(46)(47). Extracellular adenosine signals though four adenosine receptors: A1R, A2AR, A2BR, and A3R (48).…”
Section: Cd73 and Adenosine Receptor Activity Promotes Immunosuppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…With tissue damage, inflammation, and hypoxic stress, ATP is released from stressed, necrotic, and/or apoptotic cells and is hydrolyzed stepwise by ectonucleoside triphosphate diphosphohydrolase-1 (CD39), converting ATP to AMP, and CD73, converting AMP to extracellular adenosine (Figure 1). ATP's activation of ATP receptors promotes inflammation, whereas subsequent breakdown of ATP to extracellular adenosine and activation of adenosine receptors dampens inflammation (Figure 1) (45)(46)(47). Extracellular adenosine signals though four adenosine receptors: A1R, A2AR, A2BR, and A3R (48).…”
Section: Cd73 and Adenosine Receptor Activity Promotes Immunosuppressionmentioning
confidence: 99%
“…In these preclinical studies, extracellular adenosine levels and CD39, CD73, A2AR, and A2BR gene expression decreases and coincides with increased antitumor immunity (102,108). Hypoxiainducible factors (HIFs) are strongly linked to increasing CD73 (109), A2AR (110), and A2BR (111) gene expression and collaborates to increase extracellular adenosine/adenosine receptor signaling for dampening inflammation (46,47). Interestingly, recent studies show tumor cells can reprogram NK cells to gain immunosuppressive functions [e.g., increase IL-10 and transforming growth factor-β (TGF-β) production via signal transducer and activator of transcription 3 (STAT3) transcriptional activity, suppressing IFN-γ production] (112).…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…IBD, including Crohn's disease and ulcerative colitis, are characterized by disrupted epithelial barrier function, increased bacterial translocation and dysregulated immunological environment in the gut . Adaptive immunity, Th17 responses especially, plays a crucial role in the propagation of inflammation during IBD .…”
Section: Functional Roles Of Myeloid Mir‐223 During Inflammatory Disementioning
confidence: 99%
“…IBD, including Crohn's disease and ulcerative colitis, are characterized by disrupted epithelial barrier function, increased bacterial translocation and dysregulated immunological environment in the gut. [75][76][77][78][79][80][81][82][83] Adaptive immunity, Th17 responses especially, plays a crucial role in the propagation of inflammation during IBD. 84,85 On the other hand, dendritic cell (DC) and macrophages are also crucial in the maintenance of intestinal immune homeostasis.…”
Section: Mir-223 In Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…There is a lot of literature showed that hypoxia is an independent contributing factor to acute lung injury. Moreover, hypoxia can induce the body's in ammatory response, and in ammation can lead to tissue hypoxia, the two are intertwined, and in uence each other, causing acute lung injury [15][16][17][18] . Hypoxia environment has great in uence on the function of mitochondria.…”
Section: Introductionmentioning
confidence: 99%